Comprehensive Review of Sambiloto (Andrographis Paniculata) - Rohama, Rohama; Dari, Kristina Wulan; Elieser, Michael; Kristina, Isha Desty; Puspita, Melinda Dian (Universitas Ibn Khaldun Bogor, 2024)
This article provides a literature review of Sambiloto (Andrographis paniculata) covering key aspects such as raw material name, content and composition of raw material, active constituents/secondary metabolites, claimed benefits, empirical data, raw material standardization, preclinical studies, and toxicity tests. Data is sourced from various Indonesian journals and books published in the last five years to give an in-depth understanding of the benefits and potential of Sambiloto. The review results show that Sambiloto has significant health potential, but standardization and further tests are required to ensure its safety and efficacy.